DETEKSI CEMARAN Salmonella sp. PADA KOMODITAS TUNA, TONGKOL DAN CAKALANG (TTC) YANG DIJUAL DI PASAR INPRES DI DAERAH ISTIMEWA YOGYAKARTA - Ratnaningtyas, Susi; Wahyudi, Dzikri; Wulansari, Devi; Utami, Wayah Putri (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Fish is a nutrition source, mainly protein, which is easily decomposed as a result of bacterial and enzyme activity. Therefor its fish after harvest if it is not done properly will cause the fish to become damaged quickly and experience a decrease in quality because fish is a type of food that is easily subject to biological damage and is susceptible to microbial contamination (Christanti and Azhar, 2019). Incorrect handling will lead to decreased product quality. Cross contamination is one result of poor handling processes, so that the product is contaminated by pathogenic bacteria. One of the pathogenic bacteria, namely Salmonella sp. which needs to be considered for its presence in fishery products, both fresh and frozen (Ijong, Berhimpon and Sumampow, 2015). The purpose of this research is to determine the contamination of Salmonella sp. and the prevalence of contamination in Tuna, Cob and Skipjack (TTC) commodities. Final Practical Work (KPA) will be held from 14 March to 10 June 2022 at the Fish Quarantine Station, Quality Control and Safety of Fishery Products in Yogyakarta, located in Sleman Regency, Yogyakarta. The samples tested were 19 fresh fish products in the Tuna, Cob and Cakalang (TTC) commodities. Microbiological quality testing of fishery products, both fresh and frozen, needs to be carried out in order to guarantee food safety for the community. Test procedure for Salmonella sp. using conventional methods in accordance with SNI 01-2332.2-2006, which includes pre-enrichment, enrichment, isolation of bacteria or selective, observation of typical Salmonella colony morphology, isolation of pure culture of Salmonella and biochemical tests. The test results showed that all fresh fish samples taken from the InPres market in the Yogyakarta area were negative for Salmonella sp. and the prevalence is 0%. The application of good sanitation and hygiene will prevent contamination of pathogenic bacteria and still maintain the cold chain to inhibit enzyme reactions found in the fish's body. Bacterial contamination Salmonella sp. usually found in fishery products, agriculture and food products